Regina Mingotti diva and impresario at the King's Theatre, London - Burden, Michael 1960- (Royal Musical Association monographs, 2019)
Regina Mingotti was the first female impresario to run London's opera house. Born in Naples in 1722, she was the daughter of an Austrian diplomat, and had worked at Dresden under Hasse from 1747. Mingotti left Germany in 1752, and travelled to Madrid to sing at the Spanish court, where the opera was directed by the great castrato, Farinelli. It is not known quite how Francesco Vanneschi, the opera promoter, came to hire Mingotti, but in 1754 (travelling to England via Paris), she was announced as being engaged for the opera in London "having been admired at Naples and other parts of Italy, by all the Connoisseurs, as much for the elegance of her voice as that of her features". Michael Burden offers the first considered survey of Mingotti's London years, including material on Mingotti's publication activities, and the identification of the characters in the key satirical print "The Idol".